2000
DOI: 10.1074/jbc.275.8.5739
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for Amino- and Carboxyl-terminal Sequences of SPRR1 Protein in the Formation of Cross-linked Envelopes of Conducting Airway Epithelial Cells

Abstract: The small proline-rich protein, SPRR1, is a marker gene whose expression in conducting airway epithelium is elevated under a variety of conditions that enhance squamous differentiation. The purpose of this study is to elucidate the nature of the SPRR1 sequence involved in cross-linked envelope formation in a tissue/cell type, such as conducting airway epithelium, that normally does not express squamous function except after injury or maintenance in culture. For this, a Flag-SPRR1 fusion protein expression syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…LEP members contain structural similarities to known cornified envelope precursors such as SPRR1 and loricrin, including characteristic N-terminal glutamine residues which are major sites for TGase-mediated cross-linking in SPRRs (10,15,26). This similarity strongly suggests that LEP members are TGase substrates.…”
Section: Lep Genes Are Induced After Calcium-mediated Differentiationmentioning
confidence: 79%
See 1 more Smart Citation
“…LEP members contain structural similarities to known cornified envelope precursors such as SPRR1 and loricrin, including characteristic N-terminal glutamine residues which are major sites for TGase-mediated cross-linking in SPRRs (10,15,26). This similarity strongly suggests that LEP members are TGase substrates.…”
Section: Lep Genes Are Induced After Calcium-mediated Differentiationmentioning
confidence: 79%
“…The LEP N terminus resembles that of all of the above proteins and contains glutamine residues, identified in loricrin and SPRRs, as key sites for TGase activity (26)(27)(28)(29). LEPs contain proline͞lysine͞cysteine (PKC) repeats in the N-terminal half, a feature of SPRRs, followed by serine͞glycine͞cysteine-rich regions (SGC), characteristic of loricrin.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous epithelial cell proliferation and differentiation are indicated by the presence of small proline-rich proteins (SPRRs), which form the cornified envelope underlying the plasma membrane of epithelial cells. In fact, squamous differentiation of the tracheobronchial epithelial cells is only seen during injury and repair, suggesting the presence of these processes (38). Although the SPRR1 family has been observed in the lung, the SPRR2 family has not.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well established that SPRRs act as cross-bridging proteins that participate in a cross-linking process of several CCE precursor proteins, such as loricrin (constituting 50-90% of CCE proteins) and involucrin (4,24). It is worth noting that a recent study demonstrated the actual participation of SPRR1B in the cornification of proximal TBE cells (5). Therefore, we speculate that expression of SPRRs is an essential feature of SCD of distal bronchiolar cells and plays a very important role in providing a physical and chemical barrier against the environment.…”
Section: Discussionmentioning
confidence: 99%